Ageing - Pachana, Nancy A. (2021)
Tomik w zwięzły i przystępny sposób prezentuje problematykę biologicznych, psychologicznych i społecznych zmian, jakie zachodzą wraz z wiekiem. Jak dbać o siebie, żeby dożyć stu lat? Czy można zapobiec demencji? W jaki sposób technologia wspomaga osoby starsze? Ageing: A Very Short Introduction was originally published in English in 2016. This translation is published by arrangement with Oxford University Press. Wydawnictwo Uniwersytetu Łódzkiego is solely responsible for this translation from the original work and Oxford University Press shall have no liability for any errors, omissions or inaccuracies or ambiguities in such translation or for any losses caused by reliance thereon